RELATIVE RESILIENCE OF INDONESIAN SHARIA STOCK INDICES TO MACROECONOMIC, UNCERTAINTY, AND GEOPOLITICAL SHOCKS ACROSS THREE CRISIS EPISODES - Indarto, Seno; Ermawati, Wita Juwita; Suprayitno, Gendut (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
This study analyzes how Indonesia’s two main Sharia stock indices—the Jakarta Islamic Index (JII) and the Indonesia Sharia Stock Index (ISSI)—respond to macroeconomic, uncertainty, and geopolitical shocks during three major crises: the 2008 global subprime mortgage crisis, the 2015 commodity-price downturn, and the COVID-19 pandemic. The research aims to determine whether the resilience of Islamic equities in an emerging market is an inherent feature or depends on crisis type and index structure. Using monthly data on JII, ISSI, the BI Rate, inflation, the rupiah–US dollar exchange rate, world oil prices, the World Uncertainty Index, and the Geopolitical Risk Index, the study applies unit-root tests followed by an autoregressive distributed lag (ARDL) approach and error-correction models to estimate short- and long-run relationships. The results show that JII experienced the deepest contraction during the 2008 crisis, while both indices exhibited more robust recoveries in the 2015 and COVID-19 episodes. Exchange-rate movements emerge as the main transmission channel through which global shocks affect Indonesian Sharia equities, and global uncertainty and geopolitical risk exert statistically significant but episode-dependent effects on index performance. These findings indicate that Indonesian Sharia stock indices are relatively resilient yet remain vulnerable to strong external disturbances, and that their resilience is conditional on the nature of the shock and on whether the index is selective (JII) or broad-based (ISSI). The study contributes to the literature on Islamic capital markets in emerging economies and offers practical insights for portfolio diversification and macroprudential policy design under heightened global risk.